The Existence of Female Politicians in Denpasar Disaster Management - I.G.A.AG Dewi Sucitawathi P; Ni Luh Yulyana Dewi (Wacana Journal of Social and Humanity Studies, 2018)
The purpose of this study is to explain the role of female politicians in disaster management in Denpasar City. The disaster category taken in this study consists of some major disasters which severely damage public facilities and harm the community such as fire, flood, tornado and earthquake. The role of female politicians is not expected to always focus on political issues, but also requires active involvement in addressing social problems, especially disasters because disaster response in disaster management does not only require community contributions but also government contributions.The specific target to be achieved is to find out how far the level of active participation of female politicians in disaster management in Denpasar City. The involvement of female politicians is considered on pre-disaster, disaster, and post-disaster response. The female politicians referred to in this study are the regional house of representatives,Â  the cadres, and the administrators of political parties in Denpasar City. In addition, this study aims to determine the policy model formulated by female politicians in handling disasters in Denpasar City, along with their role in helping the female victims.The method used in this study consists of primary data and secondary. The primary data is obtained from the observations, interviews, and documentation whereas the secondary data is obtained from the internet, literature and scientific journals. The research stage starts from 1) Collecting data and information from the government through Regional Disaster Management Agency, the regional house of representatives, cadres and the administrators of political parties in Denpasar City. 2) Collecting data and information from people who have been the victims of disasters and those who live in the vicinity of the disaster site by distributing some questionnaires.